Lost legacy: the Mormon office of Presiding Patriarch - Bates, Irene M. (University of Illinois Press, 2018)
Charisma and authority : the crucible for the office of Patriarch -- "Like the patriarchs of old" : Joseph Smith, Sr., first patriarch, 1883-40 -- "By blessing and also by right" : Hyrum Smith, second patriarch, 1841-44 -- Office in crisis : William Smith, third patriarch, May 1845-October 1845 -- Patriarchal bridge : interregnum, 1845-47, and Uncle John Smith, fourth patriarch, 1847-54 -- Continuing the tradition : John Smith, fifth patriarch, 1855-1911 -- A question of primacy : Hyrum G. Smith, sixth patriarch, 1912-32 -- Decade of uncertainty, 1932-42, and the compromise : Joseph F. Smith II, seventh patriarch, 1942-46 -- The end of the line : Eldred G. Smith, eighth patriarch, 1947-79 -- Unique emeritus : Eldred G. Smith, patriarch/general authority emeritus, 1979-2013 -- Appendix A. presiding patriarchs and presidents of the Mormon Church -- Appendix B. Mormon presiding patriarchs